Implementasi E-Modul Pembelajaran Sejarah Fisika Menggunakan Google Site Dengan Model Pembelajaran Project Based Learning Pada Mahasiswa Fisika - Rahman, Mardia Hi; Hamid, Fatma; Isra, Hutri Handayani; Viyanti, Viyanti; Irsan, Adina; Panigfat, Marita; Sahjat, Sumarni (Universitas Khairun, 2024)
This research aims to streamline the PjBL model physics e-module assisted by Google Sites which is suitable for use for physics learning and determine the effectiveness of the PjBL model physics e-module assisted by Google Sites. Google Sites is a service owned by the Google site that facilitates its users so they can have a website easily and practically. Using Google Sites for students will make it easier for students to access teaching materials and will not need to use up smartphone memory capacity. With this convenience, lecture material can be in the form of learning links that students can access. Apart from that, students can access it anywhere and at any time so that it can be used to study independently according to lecture needs.Â This research is Research and Development research with a 4D model which includes 4 stages, namely the define, design, develop and disseminate stages. The results of the research show that the PjBL model e-module assisted by Google Sites in learning the history of physics is effectively used in learning to increase student learning independence.